2008
DOI: 10.4161/cbt.7.3.5425
|View full text |Cite
|
Sign up to set email alerts
|

Cancer gene therapy of adenovirus-mediated anti-4-1BB scFv in immunocompetent mice

Abstract: The use of immunostimulatory molecule genes aiming at enhancing anti-tumor immunity has emerged as a new approach to treat cancers. 4-1BB signaling, an important costimulatory pathway delivering a signal for T cell activation, survival and growth, has become one of the most promising targets for cancer immunotherapy. In this work, a recombinant nonreplicative adenovirus (Ad.4-1BB scFv) carrying a single-chain Fv fragments (scFv) specific for 4-1BB gene (anti-4-1BB scFv) was generated, haracterized and explored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…These anti-tumor effects of anti-4-1BB ScFv were believed to result from low-dose cyclophosphamide-mediated depletion of Tregs [101]. Similar results were obtained in studies carried out by Liu et al [102]. These authors observed that intratumoral injection of anti-4-1BB ScFV inhibited the growth of Hepa 1 --6 tumors, and this protective effect was shown to depend on increased IFN-g and increased tumor infiltration by T cells [102].…”
Section: Variants Of Anti-4-1bb In Cancer Therapysupporting
confidence: 61%
“…These anti-tumor effects of anti-4-1BB ScFv were believed to result from low-dose cyclophosphamide-mediated depletion of Tregs [101]. Similar results were obtained in studies carried out by Liu et al [102]. These authors observed that intratumoral injection of anti-4-1BB ScFV inhibited the growth of Hepa 1 --6 tumors, and this protective effect was shown to depend on increased IFN-g and increased tumor infiltration by T cells [102].…”
Section: Variants Of Anti-4-1bb In Cancer Therapysupporting
confidence: 61%
“…The reasoning behind our scFv format was to preserve the genetic source of the antibody fragment by cloning it into a phagemid vector and utilizing relatively simple production in bacteria. Furthermore, the small molecular size of scFv should provide high tissue penetration efficiency (Kioi et al, 2008;Liu et al, 2008;Stirnemann et al, 2008), and a lack of significant toxicity (Korn et al, 2004;Yang et al, 2007a;Nam et al, 2008) while giving rapid plasma clearance (Mao et al, 1999;Hamilton et al, 2002;Olafsen et al, 2004;Pavoni et al, 2006), which makes such an antibody a potentially suitable candidate for clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…37 In our previous work, adenoviruses carrying the anti-4-1BB scFv gene (Ad.4-1BB scFv) were used as an immunotherapy method to treat Hepa 1-6 tumors in C57BL/6 mice. 17 Although delay of tumor growth was observed, the antitumor efficacy was still not satisfactory. tumors after Ad.4-1BB scFv or Ad.4-1BB scFv plus CTX treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…20 reported previously. 17 The anti-4-1BB scFv was the variable region from the anti-4-1BB hybridoma 1D8. For cell surface expression of scFv and anti-4-1BB scFv detection, the transmembrane domain and cytoplasmic tail from CD80 (hCD80 Tm and cytoplasmic domain) were used and a human immunoglobulin Fc fragment (hIgG Fc) following the scFv was added.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation